ETIKA AGAMA NUSANTARA: STUDI KRITIS TERHADAP POLA INTERAKSI MASYARAKAT DESA KEBANGSAAN SITUBONDO - Nur, Achmad (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2020)
This paper is the result of scientific research on the socio-religious phenomena of the national village community in the district of Situbondo Wonorejo. The village is interesting to study because it represents a harmonious life between the existing religions. The research attempts to answer the question on how the pattern of interaction between the people of Wonorejo communicates religious and national messages in the public space. To answer this question, Habermas’ theory of communicative action is used examine how religion plays a role in the public space. The research found that first, the life patterns of the people of Wonorejo are based on three strengths, namely dogma or teachings from each religion, the power of sacredness believed by each religion, and the power of religious spirituality as a manifestation of dogma and the sacredness. All the three strengths were born from a dialogue between the beliefs of the local communities and their predecessors and the religious values that they are embracing